2014
DOI: 10.1002/ejlt.201300433
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cooking conditions on cholesterol oxidation and astaxanthin in dried salted shrimp

Abstract: Dried salted shrimp is a product made from raw shrimps, which are usually cooked and dried under direct sunlight. Brine cooking is an important step during the production of dried salted shrimp as it promotes changes that affect the product's end quality. The aim of this study was to evaluate the effect of brine concentration and boiling time on cholesterol oxidation products (COPs) formation and the concomitant changes in astaxanthin content and fatty acid profile in shrimp during cooking, sun drying, and sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 28 publications
2
10
0
Order By: Relevance
“…This may be due to the changes in structural conformations induced by salinization and the protein lost its binding affinity to small molecules including astaxanthin, thus increasing the content of free astaxanthin. However, at the same time, astaxanthin oxidized by thermal oxidation [ 44 ] and higher salt concentrations led to an increased degree of protein denaturation, and when the part of the protein bound to astaxanthin completely denatured, the degradation rate of astaxanthin would be greater than the formation rate, resulting in a decrease in the astaxanthin content at high salt concentrations (≥6%). This phenomenon can also be confirmed by the changes in protein secondary structure in Figure 5 , where the degree of protein denaturation increased when the salt concentration increased from 4% to 8%.…”
Section: Resultsmentioning
confidence: 99%
“…This may be due to the changes in structural conformations induced by salinization and the protein lost its binding affinity to small molecules including astaxanthin, thus increasing the content of free astaxanthin. However, at the same time, astaxanthin oxidized by thermal oxidation [ 44 ] and higher salt concentrations led to an increased degree of protein denaturation, and when the part of the protein bound to astaxanthin completely denatured, the degradation rate of astaxanthin would be greater than the formation rate, resulting in a decrease in the astaxanthin content at high salt concentrations (≥6%). This phenomenon can also be confirmed by the changes in protein secondary structure in Figure 5 , where the degree of protein denaturation increased when the salt concentration increased from 4% to 8%.…”
Section: Resultsmentioning
confidence: 99%
“…Although this is not an unusual distribution [14,32], 7-keto derivatives are more frequently found as the major ones, mainly in advanced stages of oxidation. This point was also critical for epoxydes behavior, which started to decrease afterwards, with betaisomers being formed in higher amounts than alpha ones, as the steric hindrance of hydroxyl group in position 3 determines [33].…”
Section: Oxysterols Distributionmentioning
confidence: 89%
“…Among these influencing factors, processing, cooking and storage conditions clearly affect the oxysterols formation [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…This fact is very important during the production of smoked salmonoids and dried salted shrimp. Studies showed that the astaxanthin content in cooked shrimp decreased by 78% after four days of direct sun drying due to photodegradation [ 46 ]. The content of this pigment was much lower than the content obtained in a jet-spouted bed-drier at 80, 100 and 120 °C [ 47 ].…”
Section: The Occurrence Structure and Industrial Potential Of Astaxanthinmentioning
confidence: 99%